Do students' errors still occur in mathematical word problem-solving?: A newman error analysis - Zulyanty, Marni; Mardia, Ainun (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Mathematical word problems can be utilized to improve students' mathematic problem-solving skills. However, students' error still occurs in mathematical word problem-solving. This research aimed to trace and reveal students' errors in problem-solving using the Newman Error Analysis stages. This research is descriptive qualitative research. The research subjects were moderate-ability students of State Madrasah Tsanawiyah (MTs) in Jambi. Mathematical word problem worksheets and interview templates were used as instruments in this research. Students with the moderate ability category were given worksheets on algebraic and the Pythagorean Theorem operation. The students were also interviewed to get more information about the errors they experienced. This research found that the students' errors during word problem-solving had implications for the incorrect answer. Students' errors occurred at the comprehension, transformation, process skill, and encoding stages of the Newman Error Analysis stages. Indeed, the Newman Error Analysis stage is a cycle that means errors at the first stage are more likely to cause errors in the next stages and lead to an incorrect answer. Furthermore, error at the comprehension stage is the most crucial error in mathematical problem-solving.